Moderate Muslim Characters in The Quran and Its Implementation in Islamic Religious Education Learning in Public Universities - Sari Narulita; Pandu Hyangsewu; Adimin Diens (Islamic Religious Education Departement, 2022)
Actions of radicalism and terrorism have hurt Muslims and placed them at fault. The teachings of jihad in Islam are often the target of accusations of being the leading cause of violence in the name of religion. Many Islamic teachings direct a Muslim to be moderate. This article explains the verses and hadiths related to Moderate Islam's character and describes the implementation process in PAI learning in public universities. This research is qualitative research by reviewing the verses of the Quran and hadith and observations on the implementation process through Islamic learning in several universities on the island of Java. The results show that the characteristics of moderate Muslims in the Quranic hadith lead to Muslims who can balance their attitudes and views. At the same time, the implementation process is realized through the PAI curriculum, which contains Islamic moderation values, supported by moderate lecturers, which directs students to understand Islamic teachings textually and contextually.